Analysis of water use on a large river basin using MIKE BASIN Model: a case study of the Abbay River Basin, Ethiopia - Wubet, F. D.; Awulachew, Seleshi Bekele; Moges, A. (2009)
The purpose of this study is to simulate water allocation for major activities (existing and planned) in the Abbay Basin using up-to-date water allocation and simulation models. The model, MIKE BASIN, is used to gain an insight into the potential downstream consequences of the development of physical infrastructure and water abstraction in a number of different future development scenarios. Seventeen irrigation projects covering an area of 220,416 hectares (ha) of land have been selected from different gauged catchments of the sub-basin in addition to 4,800 megawatt (MW) hydropower projects on the main stream of the study area (Ethiopian part of Blue Nile). From the analysis, the total water extracted for these irrigation projects was estimated to be 1.624 billion cubic meters (BCM) annually. A reduction in the border flow volume as a result of the implementation of these irrigation projects under the reservoir scenario is 3.04% of the estimated mean annual flow of 50.45 BCM. Similarly, from the analysis, the total power generated due to the development of the major hydropower projects on the main stream, having an installed capacity of 4,800 MW, is 18,432 gigawatt hours (GWh) per year. This implies, while these interventions provide significant opportunities with respect to interventions and energy generations, their impact on downstream water availability is minimal.